1992
DOI: 10.1002/tea.3660290502
|View full text |Cite
|
Sign up to set email alerts
|

The rate of acquisition of formal operational schemata in adolescence: A secondary analysis

Abstract: A theoretical model of cognitive development is applied to the study of the acquisition of formal operational schemata by adolescents. The model predicts that the proportion of adolescents who have not yet acquired the ability to perform a a specific Piagetian-like task is an exponentially decreasing function of age. The model has been used to analyze the data of two large-scale studies performed in the United States and in Israel. The functional dependence upon age was found to be the same in both countries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…As mentioned previously, the responses of children to Question 2 for subjects in Grades 4-10 were investigated by Eckstein and Shemesh (1989). In that study no clear dependence on age was found, but the improved statistics and broader range of ages in the current study does indicate dependence upon age.…”
Section: Questions 1-3supporting
confidence: 50%
See 1 more Smart Citation
“…As mentioned previously, the responses of children to Question 2 for subjects in Grades 4-10 were investigated by Eckstein and Shemesh (1989). In that study no clear dependence on age was found, but the improved statistics and broader range of ages in the current study does indicate dependence upon age.…”
Section: Questions 1-3supporting
confidence: 50%
“…Student responses to this question were investigated by Eckstein and Shemesh (1989). They found six categories of response, among which two categories were most common.…”
Section: Comments: Intuition Versus Logical Responsementioning
confidence: 99%
“…For example, significant differences among tenth-, eleventh-, and twelfth-grade students were not observed for their performance on combinatorial reasoning problems. Eckstein and Shemesh (1992) who found evidence supporting different functional dependence for problems of different reasoning modes have reported similar results. Furthermore, the present study confirms that the development and saturation of formal cognitive abilities is not complete even for twelfth-grade students (Lawson, 1985;Renner & Stafford, 1972;Shayer, Kucherman, & Wylam, 1976;Valanides, 1997a) and that a high percentage of higher secondary school students are apt to be transitional (Karplus et al, 1980;Zeidler, 1985) or even concrete reasoners (Valanides, 1997b).…”
Section: Discussionmentioning
confidence: 61%
“…
Preece (1993) made some very valuable suggestions for the modification of the mathematical model which was proposed to describe stages of cognitive development (Eckstein & Shemesh, 1992a; denoted ESI). Preece pointed out that the model cannot be extrapolated to higher or lower ages.
…”
mentioning
confidence: 99%